Quality evaluation of JAMA Patient Pages on diabetes using the Ensuring Quality Information for Patient (EQIP) tool - Vaona, Alberto; Marcon, Alessandro; Rava, Marta; Buzzetti, Roberto; Sartori, Marco; Abbinante, Crescenza; Moser, Andrea; Seddaiu, Antonia; Prontera, Manuela; Quaglio, Alessandro; Pallazzoni, Piera; Sartori, Valentina; et al. (Primary Care Diabetes, 2011)
CONTEXT: Many medical journals provide patient information leaflets on the correct use of medicines and/or appropriate lifestyles. Only a few studies have assessed the quality of this patient-specific literature. OBJECTIVE: The purpose of this study was to evaluate the quality of JAMA Patient Pages on diabetes using the Ensuring Quality Information for Patient (EQIP) tool. METHOD: A multidisciplinary group of 10 medical doctors analyzed all diabetes-related Patient Pages published by JAMA from 1998 to 2010 using the EQIP tool. Inter-rater reliability was assessed using the percentage of observed total agreement (p(o)). A quality score between 0 and 1 (the higher score indicating higher quality) was calculated for each item on every page as a function of raters' answers to the EQIP checklist. A mean score per item and a mean score per page were then calculated. DATA SUMMARY: We found 8 Patient Pages on diabetes on the JAMA web site. The overall quality score of the documents ranged between 0.55 (Managing Diabetes and Diabetes) and 0.67 (weight and diabetes). p(o) was at least moderate (>50%) for 15 of the 20 EQIP items. Despite generally favorable quality scores, some items received low scores. The worst scores were for the item assessing provision of an empty space to customize information for individual patients (score=0.01, p(o)=95%) and patients involvement in document drafting (score=0.11, p(o)=79%). CONCLUSIONS: The Patient Pages on diabetes published by JAMA were found to present weak points that limit their overall quality and may jeopardize their efficacy. We therefore recommend that authors and publishers of written patient information comply with published quality criteria. Further research is needed to evaluate the quality and efficacy of existing written health care information.